2008
DOI: 10.1063/1.2834874
|View full text |Cite
|
Sign up to set email alerts
|

An improved time-of-flight method for cluster deposition and ion-scattering experiments

Abstract: A molecular beam apparatus has been developed for deposition and scattering experiments of size-selected clusters. The new setup combines a bimetallic laser ablation cluster source with a collinear time-of-flight mass spectrometer. Mass selection is achieved with a pulsed electrostatic mirror. A significantly improved transmission in combination with a reduction of the kinetic energy distribution of the mass selected clusters has been obtained. Without further modification of the apparatus, surface-induced dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…In this paper an incident energy E i stands for the difference between the average kinetic energy of the projectile ions and the potential energy. Since the incident energy spread of the primary ion beam amounts to approximately 150 eV ͓full width at half maximum ͑FWHM͔͒, 16,19 fragmentation processes are already observed also for negative values of E i .…”
mentioning
confidence: 99%
“…In this paper an incident energy E i stands for the difference between the average kinetic energy of the projectile ions and the potential energy. Since the incident energy spread of the primary ion beam amounts to approximately 150 eV ͓full width at half maximum ͑FWHM͔͒, 16,19 fragmentation processes are already observed also for negative values of E i .…”
mentioning
confidence: 99%
“…(A study of 3-D metal clusters as catalysts in CNT growth was reported in [8], however, no CNT growth was studied therein; CNT growth derived from nm-sized, ligand-stabilized mixed metal clusters as precatalysts was reported in [9]. ) Non-agglomerated naked iron clusters of 0.6–0.9 nm size were generated, mass-selected and surface-implanted at room temperature under ultrahigh vacuum [10] at a surface coverage in the range of a few thousandths up to a few hundredths of a monolayer on standard substrate grids for transmission electron microscopy (TEM). The kinetic energy of the as deposited iron clusters is about 2550 ± 150 eV, which is sufficient for their surface implantation [11].…”
Section: Resultsmentioning
confidence: 99%
“…A number of state-of-the-art cluster deposition instruments have been built for size-selected cluster science. The list is long, but some representative instruments are the Heiz instrument and those located at EPFL, Switzerland, the University of Utah, Salt Lake City, the Technische Universität Darmstadt, Germany, and the Universidad Autónoma de Nuevo León, Mexico . The listed instruments use quadrupoles in the mass selection stage.…”
Section: Instrumentation For Ion/surface Collision Experimentsmentioning
confidence: 99%
“…Preparation and physicochemical investigations of sized-selected clusters derived from various other metals have been reported: Al, Cu, , Si, W, Ni, ,,, Ru, Mo 4 S 6 , Mo n /(MoO 3 ) n , Met-Cars, and various bimetallic clusters. ,, …”
Section: Soft Landing and Related Phenomenamentioning
confidence: 99%
See 1 more Smart Citation